A comparative analysis of factor analysis model for pinpointing agile developers. (26th June 2019) - Khatri, Alok; Garg, D.; Dangayach, G.S.
Agile manufacturing is an emerging approach of engineering to deal with dynamic demand of customer and market. The prime factors that influence agility are agile developers and enablers. Agile developers are mainly less investment factors that are basically governed by managerial power. To find out most important agile developers, a survey-based study was conducted with the aim to develop model for agility developers and measure its level in Indian manufacturing industries. It was hypotheses that sensitiveness to change, relationship with customer, relationship with supplier, flexibility and competency and responsiveness is not significant with agile manufacturing. The data were analysed by ANOVA test, different factor analysis techniques and a complete regression model for agile developer was prepared with the help of analytic hierarchy process. It was found that design excellence and decision flexibility variables have highest importance among all components and developers are being used almost at their 50% level.